Down-Regulating HAUS6 Suppresses Cell Proliferation by Activating the p53/p21 Pathway in Colorectal Cancer - Shen, Aling; Liu, Liya; Huang, Yue; Shen, Zhiqing; Wu, Meizhu; Chen, Xiaoping; Wu, Xiangyan; Lin, Xiaoying; Chen, Youqin; Li, Li; Cheng, Ying; Chu, Jianfeng; et al. (Frontiers in Cell and Developmental Biology, 2022)
Background: HAUS6 participates in microtubule-dependent microtubule amplification, but its role in malignancies including colorectal cancer (CRC) has not been explored. We therefore assessed the potential oncogenic activities of HAUS6 in CRC. Results: HAUS6 mRNA and protein expression is higher in CRC tissues, and high HAUS6 expression is correlated with shorter overall survival in CRC patients. HAUS6 knockdown in CRC cell lines suppressed cell growth in vitro and in vivo by inhibiting cell viability, survival and arresting cell cycle progression at G0/G1, while HAUS6 over-expression increased cell viability. We showed that these effects are dependent on activation of the p53/p21 signalling pathway by reducing p53 and p21 degradation. Moreover, combination of HAUS6 knockdown and 5-FU treatment further enhanced the suppression of cell proliferation of CRC cells by increasing activation of the p53/p21 pathway. Conclusion: Our study highlights a potential oncogenic role for HAUS6 in CRC. Targeting HAUS6 may be a promising novel prognostic marker and chemotherapeutic target for treating CRC patients.